Penerapan Metode Flipped Classroom Berbantuan Edmodo Pada Pembelajaran Matematika - Dian Nurjannah; Iis Holisin; Sandha Soemantri (MUST: Journal of Mathematics Education, Science and Technology, 2022)
The purpose of this study aims to describe the implementation of the Edmodo-assisted Flipped Classroom method in learning mathematics in class XI MIA 3 SMA Muhammadiyah 10 Surabaya. The method was descriptive quantitative research. The subjects were 33 students of class XI MIA 3 SMA Muhammadiyah 10 Surabaya. Data collection techniques in the implementation of the Edmodo-assisted Flipped Classroom method are questionnaires, observations, and tests. The research instrument of this study used a student response questionnaire sheet with 10 statements, a student activity observation sheet with 6 observed activities, and a test sheet was conducted by giving quiz questions through Edmodo as many as 5 multiple choice questions. The results showed that 85% of students completed so that learning achievement was very good, student responses resulted in an average of 82% which could be said to be very positive, and student activities in this study resulted in 30% of students being said to be active and 61% of students being said to be quite active.